2021
DOI: 10.1051/matecconf/202134303008
|View full text |Cite
|
Sign up to set email alerts
|

Numerical-Experimental Study Regarding the Single Point Incremental Forming Process

Abstract: The present paper proposes a numerical-experimental comparative study on the single point incremental forming process. A DC04 steel sheet with a thickness of 0.6 mm was used for both the numerical simulation using the finite element method and the experimental research. The type of trajectory used was a spiral trajectory and the finished part obtained was a truncated cone-shaped part. The analysis program used for simulation was Ls-Dyna. The simulations were performed in several variants: with a fixed mesh and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…This conclusion is also reflected in Figure 10. Rosca et al [54] indicated that the in-plane force oscillates between maximum and minimum values, shifted relative to each other, depending on the position of the forming tool. Formisano et al [55] concluded that the oscillations are due to a little variability in the stiffness of the sheet, since during a spiral the distance of the tool from the frame is different and, with it, the mechanical reaction of the sheet [55].…”
Section: Resultsmentioning
confidence: 99%
“…This conclusion is also reflected in Figure 10. Rosca et al [54] indicated that the in-plane force oscillates between maximum and minimum values, shifted relative to each other, depending on the position of the forming tool. Formisano et al [55] concluded that the oscillations are due to a little variability in the stiffness of the sheet, since during a spiral the distance of the tool from the frame is different and, with it, the mechanical reaction of the sheet [55].…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the maximum predication force is (25.9 KN) and the maximum predication thickness reduction is (46 %). In another work, Rosca et al [11] conducted a numerical-experimental study of the single-point incremental forming process. The sheet metal is steel (DC04) with a thickness of 0.6 mm, and the geometry produced is a truncated cone.…”
Section: Figurementioning
confidence: 99%